2004
DOI: 10.1093/cercor/bhh095
|View full text |Cite
|
Sign up to set email alerts
|

Control of Object-based Attention in Human Cortex

Abstract: Visual attention is a mechanism by which observers select relevant or important information from the current visual array. Previous investigations have focused primarily on the ability to select a region of space for further visual analysis. These studies have revealed a distributed frontoparietal circuit that is responsible for the control of spatial attention. However, vision must ultimately represent objects and in real scenes objects often overlap spatially; thus attention must be capable of selecting obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
190
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(218 citation statements)
references
References 51 publications
27
190
0
1
Order By: Relevance
“…Specifically, we asked whether (i) parietal cortex issues a brief transient signal after an instruction to shift one's spatial attention (12); (ii) this reorienting signal is differentially sensitive to object-based properties of the attended items (i.e., giving rise to the object-based advantage); and (iii) the effects of reorienting attention to a within-object versus a between-object location results in distinctive cortical activation patterns in earlier regions of visual cortex. We observed that blood oxygenation level-dependent (BOLD) activity in the posterior parietal cortex was enhanced after instructions to shift versus to hold attention (i.e., spatial attention), replicating existing findings (12,16,21,22) and verifying that our paradigm successfully engages neural mechanisms of attentional shifts. However, the first important finding was that the space-based versus object-based attentional shifts are mediated by separable neural substrates: specifically, enhanced activity for within-object over between-object shifts of attention was observed in the left posterior parietal cortex, suggesting that this cortical region expressly subserves objectbased attentional selection.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Specifically, we asked whether (i) parietal cortex issues a brief transient signal after an instruction to shift one's spatial attention (12); (ii) this reorienting signal is differentially sensitive to object-based properties of the attended items (i.e., giving rise to the object-based advantage); and (iii) the effects of reorienting attention to a within-object versus a between-object location results in distinctive cortical activation patterns in earlier regions of visual cortex. We observed that blood oxygenation level-dependent (BOLD) activity in the posterior parietal cortex was enhanced after instructions to shift versus to hold attention (i.e., spatial attention), replicating existing findings (12,16,21,22) and verifying that our paradigm successfully engages neural mechanisms of attentional shifts. However, the first important finding was that the space-based versus object-based attentional shifts are mediated by separable neural substrates: specifically, enhanced activity for within-object over between-object shifts of attention was observed in the left posterior parietal cortex, suggesting that this cortical region expressly subserves objectbased attentional selection.…”
supporting
confidence: 86%
“…The focus of this study is on elucidating the neural mechanisms subserving attentional selection, but with more specific emphasis on differentiating between the neural substrate of space-based and object-based attention. In particular, we trace the neural signal that gives rise to an advantage for selected space-based versus object-based information from the source of the attentional selection to its effects (modulations) in primary sensory cortex.Although much progress has been made in understanding the behavioral mechanisms mediating attentional selection, most neurophysiological studies have focused solely on space-based attentional selection (4, 11-15), with few exceptions (10,(15)(16)(17)(18). To examine and distinguish between the neural bases of spacebased and object-based attentional selection, we used functional MRI to address two main goals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This activation is believed to reflect discrimination of distracters from targets and diversion of attention from distracters (Bledowski et al, 2004). Previous fMRI studies found that activity in the FEF is associated with the diversion of attention in space (Astafiev et al, 2003;Hopfinger et al, 2000), the shifting of attention between objects at the same location, and between features of the same object (Liu et al, 2003;Serences et al, 2004). Activity of FEF neurons mediates selection, generation, and inhibition of responses after peripheral cues (Astafiev et al, 2003;Connolly et al, 2002;Merriam et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the FFA responds to faces more when attention is directed to faces as compared to places or other object categories (Serences, Schwarzbach, Courtney, Golay, & Yantis, 2004;O'Craven, Downing, & Kanwisher, 1999;Wojciulik, Kanwisher, & Driver, 1998). In other words, voluntary object-based attention increases FFA activity.…”
mentioning
confidence: 99%